Role of pre-operative serum IL-6 and CA-125 in the prediction of malignant ovarian tumor - Ara, Rowson; Begum, Shirin Akter; Khatoon, Farhana; Amatullah, Mehriban; Meher, Subrina; Sultana, Anjuman; Akther, Moushume; Nihar, Fatema; Sayed, Sunzia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Ovarian cancer is the most lethal gynecological malignancy. The present study was therefore designed to determine the accuracy of IL-6 and CA-125 in the early diagnosis of malignant ovarian tumors. The aim of the study was to evaluate the predictive value of pre-operative serum IL-6 and CA-125 levels in identifying malignant ovarian tumors. Methods: This cross-sectional study took place at BSMMU and NICRH in Dhaka, Bangladesh, from February 2022 to January 2023. It involved 94 women undergoing surgery for suspected ovarian tumors. The Mann-Whitney test was used to compare IL-6 and CA-125 levels between groups. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy were calculated to correlate serum markers with histopathological diagnoses. Statistical analysis used SPSS version 23.0 with significance set at p<0.05. Results: The study involved 94 patients with ovarian tumors, where the mean age was higher in those with malignant tumors. The most common malignant histopathological finding was serous carcinoma (34%), while benign tumors often included endometriotic cysts (12.8%) and mucinous cystadenomas (10.6%). Elevated levels of IL-6 and CA-125 were significantly associated with malignant tumors (p<0.05). Both IL-6 and CA-125 showed high diagnostic accuracy in identifying malignant ovarian tumors when used alone or in combination, as indicated by receiver-operator characteristic curves. Conclusions: Serum IL-6 shows higher sensitivity and specificity for detecting malignant ovarian tumors, both epithelial and non-epithelial, making it a valuable diagnostic tool alongside CA-125 in assessing suspicious ovarian masses.